Visual Branding Strategies in Indonesian Coffee Shops and Street Food Vendors: A Semiotic and Thematic Analysis - Purnamasari, Ratih Pitria; Affandi, Dodi (Program Studi Manajemen Institut Manajemen Koperasi Indonesia Bandung, 2025)
This study examines visual branding strategies in Indonesian coffee shops and street food vendors, focusing on colour schemes, typography, symbolism, and design complexity in shaping brand identity and consumer perception. As competition in the food and beverage (F&B) industry intensifies, small businesses rely on visual identity for customer attraction and differentiation. A qualitative visual content analysis was conducted on 40 logos (25 from coffee shops and 15 from street food vendors) collected from GoFood, GrabFood, ShopeeFood, Instagram, and official business websites. The study applied semiotic and thematic visual analysis, coding logos based on colour psychology, typography style, symbolism, and design complexity. Two independent coders reviewed the data, achieving an inter-coder reliability score of 0.85 (Cohen's Kappa). The findings reveal that coffee shop logos favor minimalist aesthetics, featuring earthy tones (brown, green, cream), serif typography, and coffee-related symbols to convey premium quality and artisanal craftsmanship. In contrast, street food vendor logos use bold colours (red, yellow, orange), playful typography, and culturally significant symbols to enhance visibility, stimulate appetite, and reinforce authenticity. These results confirm the psychological impact of visual branding, where warm colors drive impulse purchases, while muted tones foster trust and long-term engagement. This study provides practical insights for small business owners, branding professionals, and graphic designers, emphasizing strategic alignment between visual branding and target market expectations. Future research should explore digital branding, cross-cultural branding, and multimodal brand identity strategies to develop a more comprehensive understanding of F&B visual communication.